Exploring Uniformity of Clinical Judgment: A Vignette Approach to Understanding Healthcare Professionals' Suicide Risk Assessment Practices. Issue 6 (28th September 2022) - Sequeira, Lydia; Strudwick, Gillian; De Luca, Vincenzo; Strauss, John; Wiljer, David
Abstract : Objectives: Suicide risk assessment often requires health professionals to consider a complex interplay of multiple factors, with a significant reliance on judgment, which can be influenced by factors such as education and experience. Our study aimed at assessing the uniformity of decision making around suicide risk within healthcare professionals. Methods: We used a factorial survey approach to gather information on healthcare professionals' demographics, clinical experience, and their decision on 3 vignettes of patients with suicidal ideation. We used Kruskal-Wallis tests for determining if there were significant differences between groups for continuous variables and Spearman rank correlation for measuring the association between continuous variables. Content analysis was used for analyzing free-text comments. Results: Responses were gathered from 79 healthcare professionals (nurses, nurse practitioners, physicians) who worked in primary care, mental health, or emergency department settings. Median suicide risk rates across all respondents were 90%, 50%, and 53% for vignettes 1, 2, and 3, respectively. Confidence in healthcare professionals' decisions was significantly associated with the clinical designation and personal risk profile of the healthcare professional in certain vignettes, with nurses and those willing to take more risks having a higher confidence in their decisions for vignettes 1 and 3, respectively. Treatment decision was significantly associated with mental health experience (i.e., those with lengthier mental health experiences were less likely to choose "admit to psychiatry ward" for vignette 2), clinical designation (i.e., nurses were more likely to "admit to psychiatry ward" for vignette 1), and practice setting. It should be noted that these associations were not consistent across all 3 vignettes, and results for each association were only specific to 1 of the 3 vignettes. Discussion: Findings compare decision-making practices for suicide risk assessment across several types of healthcare professions over a range of practice settings, with the high-risk vignette showing the least variability. Insights from this study are relevant when building clinical decision support systems for suicide risk assessment. Designers should think about incorporating tailored messaging and alerts to health professionals' mental health experience and/or designation. Conclusions: Within our Canadian sample, there was considerable variability among healthcare professionals assessing the risk of suicide, with important implications for tailoring education and decision support.